Math, asked by officialvermasqueen, 9 months ago

answer my question very very fastanswer question number 35th ​

Attachments:

Answers

Answered by avanisanglikar1909
0

Answer:

a) \frac{32p^4 - 1 + p^2}{32}

b) y^4 - 42 + y^2

Step-by-step explanation - part (a)

(p^2 - \frac{1}{4} ) (p^2 + \frac{1}{8} )\\= p^2(p^2 +\frac{1}{8} ) - \frac{1}{4} (p^2 + \frac{1}{8} )\\= p^4 + \frac{p^2}{8} - \frac{p^2}{4} - \frac{1}{32} \\= p^4 - \frac{1}{32} - \frac{p^2 - 2p^2}{8} \\= p^4 - \frac{1}{32} + \frac{p^2}{8}  \\

After this (optional):

\frac{32p^4 - 1 + p^2}{32}

Step-by-step explanation - part (b)

(y^2 - 6) (y^2 + 7)\\= y^2(y^2 + 7) - 6(y^2 + 7)\\= y^4 + 7y^2 - 6y^2 - 42\\= y^4 - 42 + y^2

That's it :)

Hope this helps :D

Similar questions